Digging up biblical history ; v. 2 recent archaeology in Palestine and its bearing on Old Testament - Duncan, John Garrow, 1872-1951 (London, UK Soociety for Promoting Christian Knowledge, 1931)
Contents : v. 2 : Hebrew and Canaanite domestic architecture c. 2500-100 BC - Religion -- Cave dwellers - Inscriptions - Burial customs - Work in stone and metal. Includes bibliographical references, indexes, illustrations, etc.
The Croall Lectures for 1928-29, amplified
Keywords: Bible. O.T. -- antiquities; Prehistoric peoples -- Palestine; Palestine -- antiquities